ESG Decoupling, Political Connections And Stock Price Crash Risk Evidence From Indonesian Listed Firms - Dinah Diyanah Burhan; Amiruddin; Darmawati (Pondok pesantren As-salafiyah As-Safi'iyyah, 2026)
This study investigates the effect of ESG Decoupling on Stock Price Crash Risk (SPCR) and examines the moderating role of Political Connections among non-financial firms listed on the Indonesia Stock Exchange. ESG Decoupling refers to the divergence between sustainability disclosure and actual environmental, social, and governance performance, reflecting the extent to which firms engage in symbolic sustainability reporting. Drawing upon Positive Accounting Theory, Legitimacy Theory, Signaling Theory, and the Bad News Hoarding Theory, this study argues that ESG Decoupling increases information asymmetry and encourages the accumulation of undisclosed adverse information, thereby elevating future stock price crash risk. The study employs a quantitative research design using panel data from 142 non-financial firms during the 2018–2024 period, resulting in 994 firm-year observations. ESG Disclosure Scores are obtained from Bloomberg, ESG Performance Scores from Refinitiv Eikon, and political connection data are manually collected from annual reports and corporate governance disclosures. Fixed-effects regression models are used to test the hypotheses, while System Generalized Method of Moments estimation is employed to address potential endogeneity concerns. The empirical results indicate that ESG Decoupling has a positive and statistically significant effect on Stock Price Crash Risk. Political Connections strengthen this relationship, suggesting that politically connected firms experience more severe adverse consequences when sustainability disclosures diverge from actual ESG performance. Robustness analyses using alternative measurements and dynamic specifications confirm the consistency of the findings. The study contributes to the emerging ESG literature by demonstrating that disclosure credibility represents a critical determinant of market stability and by highlighting the governance risks associated with political affiliations in emerging capital markets.